Structuring and implementation of the principal components analysis as criteria for determining the inputs and outputs to be considered in a financial analysis (2019)
This paper describes the mathematical structure of the Principal ComponentAnalysis (PCA) and an application in the metal-mechanical sector in Colombia.The analytical and numerical procedure used, is detailed to find the principalcomponents. It emphasizes in the "square matrix QR algorithm" procedure forcalculating its own values `` and vectors which reduce the variables to beanalyzed. The Principal Component Analysis is a statistical approach thatsimplifies the subjectivity of business decision makers, through theimplementation of linear algebra and numerical analysis in reducing variables toanalyze financial studies. The financial behavior of companies in the metalmechanical sector 2009-2010 can be explained by the operating profit, noncurrent liabilities and non-operating income.